Are Changing Constituencies Driving Rising Polarization in the U.S. House of Representatives? - Sussell, Jesse (RAND Corporation, 2015)
This report addresses two questions: first, whether the spatial distribution of the American electorate has become more geographically clustered over the last 40 years with respect to party voting and socioeconomic attributes; and second, whether this clustering process has contributed to rising polarization in the U.S. House of Representatives.